Um estudo do comportamento altruísta: análise comparativa entre brasileiros e asiáticos - Ferreira, Mariana de Moraes (2022)
The present study sought to investigate altruistic behaviour, comparing its manifestation in different cultures: one Western, observing Brazilians, and the other Asian, with Indians, Chinese, Japanese and a Vietnamese. This investigation aimed to establish similarities and divergences between the two groups (Brazilians and Asians) in order to verify whether there are significant differences between the populations, or whether altruism manifests itself homogeneously in all of them. To access altruistic manifestations among individuals, the Self-reported Altruism Scale (SHAS) was used, in which the participant indicates the frequency with which he/she engages in altruistic behaviors using the categories "Never", "Rarely", "Sometimes", "Frequently", and "Always", paired with the presentation of two problem-questions involving more or less altruistic choices: a decision-making question in a scenario related to mask use in the COVID-19 pandemic; and the dictator's economic game. For socioeconomic data collection, the multinational scale, the Water, Assets, Maternal Education and Household Income Index (WAMI Index) was used. No significant difference was found between the groups, so it was not possible to state that Brazilians are more altruistic than Asians or vice versa. Despite its limitations, this work served as an extended way of assessing altruism and could confirm an already existing relationship between increasing age and altruism. In addition to showing that the use of economic games in psychology can be very interesting and thus encourage further research on altruism